The nuclear stellar disc of the Milky Way: a dynamically cool and metal-rich component possibly formed from the central molecular zone - Schultheis, Mathias; Fritz, T. K.; Nandakumar, G.; Rojas-Arriagada, A.; Nogueras-Lara, F.; Feldmeier-Krause, A.; Gerhard, O.; Neumayer, N.; Patrick, L. R.; Prieto, M. A.; Schödel, R.; Mastrobuono-Battisti, A.; et al. (Astronomy and astrophysics, 2021)
Context. The nuclear stellar disc (NSD) is, together with the nuclear star cluster (NSC) and the central massive black hole, one of the main components in the central parts of our Milky Way. However, until recently, only a few studies of the stellar content of the NSD have been obtained owing to extreme extinction and stellar crowding. Aims. We study the kinematics and global metallicities of the NSD based on the observations of K/M giant stars via a dedicated KMOS (VLT, ESO) spectroscopic survey. Methods. We traced radial velocities and metallicities, which were derived based on spectral indices (Na I and CO) along the NSD, and compared those with a Galactic bulge sample of APOGEE (DR16) and data from the NSC. Results. We find that the metallicity distribution function and the fraction of metal-rich and metal-poor stars in the NSD are different from the corresponding distributions and ratios of the NSC and the Galactic bulge. By tracing the velocity dispersion as a function of metallicity, we clearly see that the NSD is kinematically cool and that the velocity dispersion decreases with increasing metallicity contrary to the inner bulge sample of APOGEE (|b|< 4°). Using molecular gas tracers (H2CO, CO(4−3)) of the central molecular zone (CMZ), we find an astonishing agreement between the gas rotation and the rotation of the metal-rich population. This agreement indicates that the metal-rich stars could have formed from gas in the CMZ. On the other hand, the metal-poor stars show a much slower rotation profile with signs of counter-rotation, thereby indicating that these stars have a different origin. Conclusions. Coupling kinematics with global metallicities, our results demonstrate that the NSD is chemically and kinematically distinct with respect to the inner bulge, which indicates a different formation scenario.